The Strategic Role of Character Education In Forming The Legal Culture of Law Students As Prospective Law Enforcement Officers - Panggung Handoko (International Journal of Educational Research & Social Sciences, 2026)
Character education in the formation of legal culture plays a strategic role in shaping law students as prospective law enforcers who are not only academically competent but also possess moral integrity, social responsibility, and sensitivity to justice. This study highlights the urgency of character education to instill honesty, responsibility, discipline, empathy, and moral courage, as well as the importance of a healthy legal culture so that students understand the law as a means of protecting society. The research method used is normative juridical with a conceptual and literature approach. The results of the study indicate that character education integrated with legal learning, legal clinics, moot courts, ethical reflection, and community service can shape prospective law enforcers who are ethical, intelligent, and responsible.